The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1093/ofid/ofad121
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex High-Definition Polymerase Chain Reaction Assay for the Diagnosis of Tick-borne Infections in Children

Abstract: Background Ixodes scapularis ticks can carry Borrelia species as well as other pathogens that cause human disease. The frequency of tick-borne infections and co-infections in children with suspected Lyme disease is unknown, creating clinical uncertainty about the optimal approach to diagnosis. Methods We enrolled children aged 1 to 21 years presenting to one of eight Pedi Lyme Net emergency departments for evaluation of Lyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…Therefore, clinicians may select doxycycline to cover Borrelia as well as other bacterial coinfections. Using a multiplex highdefinition polymerase chain reaction assay (HDPCR), we previously found that only a minority of children with Lyme disease had a tick-borne coinfection, suggesting that the primary reason doxycycline was prescribed was for Lyme disease treatment (Nigrovic et al, 2023b). The optimal approach to the diagnosis and treatment of children with potential tick-borne co-infections requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, clinicians may select doxycycline to cover Borrelia as well as other bacterial coinfections. Using a multiplex highdefinition polymerase chain reaction assay (HDPCR), we previously found that only a minority of children with Lyme disease had a tick-borne coinfection, suggesting that the primary reason doxycycline was prescribed was for Lyme disease treatment (Nigrovic et al, 2023b). The optimal approach to the diagnosis and treatment of children with potential tick-borne co-infections requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of PCR is that most assays test for only a single agent, thus preventing the detection of co-infections. To overcome this shortcoming, multiplex PCR assays have been developed that can test for several tick-borne pathogens in a single assay [166][167][168][169]. This approach simplifies TBD testing and has even led to the discovery of novel tick-borne pathogens [38,62,170].…”
Section: Molecular Methodsmentioning
confidence: 99%